A computer-aided design method for preparing copper alloy thin plates by direct powder rolling

Through computer-aided design and finite element simulation optimization of powder rolling process, the problems of complex preparation process and unstable forming quality of copper alloy thin plates are solved, and efficient and low-cost preparation of copper alloy thin plates are achieved to meet the high strength of lead frame materials and High conductivity requirements.

CN114492105BActive Publication Date: 2024-12-27XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111588661.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-23
Publication Date
2024-12-27
Estimated Expiration
2041-12-23

AI Technical Summary

Technical Problem

The existing copper alloy thin plate preparation process is complex and the molding quality is unstable, resulting in high investment costs and long production cycles, making it difficult to meet the requirements of lead frame materials for high strength, high conductivity and good processability.

Method used

Using a direct powder rolling method with computer-aided design, the electrolytic Cu powder and zirconia balls are mixed, and the finite element simulation is performed using the Drucker-Prager/Cap model to adjust the powder grading, rolling speed and rolling gap to ensure the thin copper alloy plate molding density and strength.

Benefits of technology

It realizes efficient and low-cost preparation of copper alloy thin plates, with an average relative density of more than 80%, and its strength meets the requirements of the sintering process. The thin plates are not easy to break, providing a low-cost and high-efficiency IC lead frame preparation solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114492105B_ABST
    Figure CN114492105B_ABST
Patent Text Reader

Abstract

The invention discloses a computer-aided design copper alloy thin plate direct powder rolling preparation method, which comprises the following steps: weighing electrolytic Cu powder and zirconium oxide balls, putting the electrolytic Cu powder and the zirconium oxide balls into a mixing bottle of a three-dimensional vibration powder mixer for mixing, wherein the vibration frequency of the powder mixer is 40 Hz during mixing, and obtaining mixed powder A; putting the mixed powder A into a mold, adjusting a plurality of pressures for pressing respectively, and forming blanks B corresponding to the plurality of pressures; dividing the blanks B into a plurality of cylindrical samples respectively, performing uniaxial compression on the cylindrical samples respectively by a universal testing machine, performing radial compression on the blanks B, and calculating two kinds of fracture strength respectively; calculating and analyzing the fracture strength, inputting the calculated value into finite element software for simulation calculation, and outputting a simulated density cloud map; adjusting parameters, and determining guiding parameters for direct powder rolling according to the simulated density cloud map; and solving the problems of complex process and unstable green blank quality in the alloy thin plate preparation process in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation, and in particular relates to a computer-aided design copper alloy thin plate direct powder rolling preparation method. Background Art

[0002] As integrated circuits develop towards lightweight, miniaturization and high integration, the number of pins per unit area of ​​the lead frame increases and the pitch becomes smaller, which puts higher requirements on the lead frame material, such as high strength, high conductivity and good processability. The current mainstream lead frame material is copper alloy sheet, which is usually 0.1mm thick. The traditional manufacturing method is a combination of thermomechanical processing such as casting and forging. A series of complex processes will lead to problems such as increased equipment investment costs and long production cycles. This feature greatly limits the development and application of copper alloy sheets.

[0003] Direct powder rolling can obtain near-net-shape billets without adding binders, but there are many factors that affect the rolling process. One of them is the physical properties of the powder, such as shape, size, bulk density, fluidity, hardness and compression performance. Another is the geometric parameters of the equipment, including roll diameter, rolling speed, gap, bite angle and roll surface roughness. The selection of rolling parameters is always based on empirical methods, which makes it difficult to ensure stable forming quality. Summary of the invention

[0004] The purpose of the present invention is to provide a computer-aided design copper alloy sheet direct powder rolling preparation method, which solves the problems of complex process and unstable green billet quality in the alloy sheet preparation process in the prior art.

[0005] The technical solution adopted by the present invention is a computer-aided design method for preparing copper alloy thin plates by direct powder rolling, which is specifically implemented according to the following steps:

[0006] Step 1, weighing electrolytic Cu powder and zirconium oxide balls with a particle size of 150 μm-74 μm, putting the electrolytic Cu powder and zirconium oxide balls into a mixing bottle of a three-dimensional vibration powder mixer and mixing for 2 hours, the vibration frequency of the powder mixer during mixing is 40 Hz, to obtain mixed powder A;

[0007] Step 2: Put the mixed powder A into the mold, adjust various pressures and press them respectively to form the green bodies B corresponding to the various pressures;

[0008] Step 3, the blank B is divided into a plurality of cylindrical specimens, and the cylindrical specimens are subjected to uniaxial compression by a universal testing machine, and the blank B is subjected to radial compression, and two fracture strengths are calculated respectively;

[0009] Step 4, calculating and analyzing the fracture strength obtained in step 3, inputting it into finite element software for simulation calculation, and outputting a simulation density cloud map;

[0010] Step 5: Adjust the parameters and determine the guiding direct powder rolling parameters according to the simulated density cloud map.

[0011] The present invention is also characterized in that:

[0012] In step 1, the mass ratio of electrolytic Cu powder to zirconia balls is 1:1, the ratio of large balls to small balls is 4:1, the diameter of the large balls is 9-11 mm, and the diameter of the small balls is 5-6 mm.

[0013] The specific process of step 2 is: select multiple YG8 carbide steel molds with a diameter of 25 mm, put the mixed powder A into the molds respectively, set multiple pressure values ​​in the range of 100-400 MPa, and the pressure difference between two adjacent values ​​is 50 MPa. Apply different pressures to each mold respectively, maintain uniform pressure during the pressing process, and hold the pressure for 1 min to obtain the blank B under multiple pressures.

[0014] Step 3: The height-to-diameter ratio of the cylindrical specimen is 2:1, the height is 6 mm, the diameter is 3 mm, and the compression rate is kept constant at 0.25 mm / min during uniaxial compression.

[0015] The arc loading angle of the radial compression mold used in step 3 radial compression is 20°, and the experimental constant compression rate is 0.25 mm / min.

[0016] The specific process of step 4 is as follows:

[0017] Step 4.1. Calculate the cohesion d, friction angle β and hardening curve P related to volume plasticity in the Drucker-Prager / Cap model from the fracture strength b ;

[0018] Step 4.2. Cohesion d, friction angle β and hardening curve P related to volume plasticity b Input the Drucker-Prager / Cap model into the finite element software, and use the actual rolling mill as a prototype to establish a rigid roll in the finite element software;

[0019] Step 4.3, use two rigid rollers in the finite element software to simulate the three stages of the rolling process, the first stage is the free flow zone, the second stage is the bite zone, and the third stage is the deformation and hardening zone; in the second stage, a deformable body curved trapezoidal model is established in the bite zone with a bite angle range of 7-9°, and the Drucker-Prager / Cap model parameters are assigned to the deformable body curved trapezoidal model, and its mesh type is an 8-node hexahedral linear reduced integration unit; and set the rolling speed of the rigid roller to 35-50rpm, the rolling gap to 0.1-0.25mm, and output the density cloud map.

[0020] Step 5: adjusting the parameters refers to adjusting the particle size of the electrolytic Cu powder, the rolling speed of the rigid roller, and the rolling gap.

[0021] The beneficial effects of the present invention are:

[0022] The present invention discloses a method for preparing copper alloy thin plates by direct powder rolling with computer-aided design. The deformation behavior of metal powder in the direct rolling process is studied by finite element simulation using the Drucker-Prager / Cap model. The order of influence of various process factors on the quality of green billet forming is obtained as follows: powder gradation > rolling speed > rolling gap. Under the guidance of the direct powder rolling simulation results, the average relative density of the green billet obtained by the direct powder rolling experiment is between 7.5 and 8.0 g / cm 3 , which is higher than 80% of the theoretical density, and its strength meets the transfer process of the sintering process, and the thin plate will not break. The modeling method, the physical parameter acquisition method and the numerical simulation results can be used to guide the rapid forming of the direct powder rolling process. The present invention provides basic knowledge for the direct rolling process of metal powders and provides theoretical guidance for the preparation of low-cost and high-efficiency IC lead frames. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1a is a schematic diagram of the direct powder rolling process used in the present invention;

[0024] Figure 1b The present invention uses direct powder rolling finite element model mesh diagram;

[0025] Figure 2a is a simulated density distribution cloud diagram of the copper sheet obtained in Example 1 of the present invention;

[0026] Figure 2b is a macroscopic morphology of the copper sheet obtained in Example 1 of the present invention;

[0027] Figure 2c is an experimental density distribution cloud diagram of the copper sheet obtained in Example 1 of the present invention;

[0028] Figure 3ais a simulated density distribution cloud diagram of the copper sheet obtained in Example 2 of the present invention;

[0029] Figure 3b is a macroscopic morphology of the copper sheet obtained in Example 2 of the present invention;

[0030] Figure 3c is an experimental density distribution cloud diagram of the copper sheet obtained in Example 2 of the present invention;

[0031] Figure 4a is a simulated density distribution cloud diagram of the copper sheet obtained in Example 3 of the present invention;

[0032] Figure 4b is a macroscopic morphology of the copper sheet obtained in Example 3 of the present invention;

[0033] Figure 4c is an experimental density distribution cloud diagram of the copper sheet obtained in Example 3 of the present invention;

[0034] Figure 5a is a simulated density distribution cloud diagram of the copper sheet obtained in Example 4 of the present invention;

[0035] Figure 5b is a macroscopic morphology of the copper sheet obtained in Example 4 of the present invention;

[0036] Figure 5c It is the experimental density distribution cloud diagram of the copper sheet obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0037] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0038] The present invention provides a method for preparing a copper alloy thin plate by direct powder rolling with computer-aided design, which is specifically implemented according to the following steps:

[0039] Step 1, weighing electrolytic Cu powder and zirconia balls with a particle size of 150 μm-74 μm, the mass ratio of electrolytic Cu powder to zirconia balls is 1:1, the ratio of large balls to small balls is 4:1, the diameter of large balls is 9-11 mm, and the diameter of small balls is 5-6 mm; putting the electrolytic Cu powder and zirconia balls into a mixing bottle of a three-dimensional vibration powder mixer and mixing for 2 hours, the vibration frequency of the powder mixer during mixing is 40 Hz, to obtain mixed powder A;

[0040] Step 2. Select multiple YG8 carbide steel molds with a diameter of 25 mm, put the mixed powder A into the molds respectively, set multiple pressure values ​​in the range of 100-400 MPa, and the pressure difference between two adjacent pressures is 50 MPa. The greater the pressure, the denser the green body B. Different powder particle deformation characteristics can be reflected under different pressures. Apply different pressures to each mold respectively, maintain uniform pressure during the pressing process, and hold the pressure for 1 minute. The holding time should not be too short. If it is too short, the powder particles will not form a good mechanical bond, and the green body B under multiple pressures will be obtained.

[0041] Step 3, the blank B is divided into a plurality of cylindrical specimens, the height-to-diameter ratio of the cylindrical specimen is 2:1, the height is 6 mm, and the diameter is 3 mm. The cylindrical specimens are subjected to uniaxial compression by a universal testing machine, and the blank B is subjected to radial compression. During the uniaxial compression, a constant compression rate of 0.25 mm / min is maintained. During the radial compression, the arc loading angle of the radial compression mold used is 20°, and the experimental constant compression rate is 0.25 mm / min. Two fracture strengths are calculated respectively;

[0042] Step 4: Calculate and analyze the data obtained in step 3, input it into the finite element software for simulation calculation, and output the simulated density cloud map; the specific process is:

[0043] Step 4.1. Calculate the cohesion d, friction angle β and hardening curve P related to volume plasticity in the Drucker-Prager / Cap model from the fracture strength b ;

[0044] Step 4.2. Cohesion d, friction angle β and hardening curve P related to volume plasticity b Input the Drucker-Prager / Cap model into the finite element software, and use the actual rolling mill as a prototype to establish a rigid roll in the finite element software;

[0045] Step 4.3: Use two rigid rollers to simulate the three stages of the rolling process in the finite element software, such as Figure 1a As shown in the figure, the first stage is the free flow zone, the second stage is the bite zone, and the third stage is the deformation and hardening zone. In the second stage, a deformable body curved edge trapezoidal model is established in the bite zone (such as Figure 1a The Drucker-Prager / Cap model parameters are assigned to the deformable body curved-edge trapezoidal model, and its mesh type is an 8-node hexahedral linear reduced integration unit (such as Figure 1b and set the rolling speed of the rigid roller to 35-50rpm, the rolling gap to 0.1-0.25mm, and output the simulated density cloud map. Step 5: Adjust the parameters and determine the guiding direct powder rolling parameters according to the simulated density cloud map.

[0046] Adjustment parameters refer to adjustment of electrolytic Cu powder particle size, rigid roller rolling speed, and rolling gap.

[0047] Example 1

[0048] The present invention provides a method for preparing a copper alloy thin plate by direct powder rolling with computer-aided design, which is specifically implemented according to the following steps:

[0049] Step 1, weighing electrolytic Cu powder with a particle size of 150 μm and zirconia balls, the mass ratio of electrolytic Cu powder to zirconia balls is 1:1, the ratio of large balls to small balls is 4:1, the diameter of the large balls is 11 mm, and the diameter of the small balls is 5 mm; putting the electrolytic Cu powder and zirconia balls into a mixing bottle of a three-dimensional vibration powder mixer and mixing for 2 hours, the vibration frequency of the powder mixer during mixing is 40 Hz, to obtain mixed powder A;

[0050] Step 2. Select multiple YG8 carbide steel molds with a diameter of 25 mm, put the mixed powder A into the molds respectively, set the pressure values ​​to 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, and 400 MPa, respectively, apply different pressures to each mold, maintain uniform pressure during the pressing process, and hold the pressure for 1 min to obtain the blank B under 7 pressures.

[0051] Step 3, the blank B under 7 pressures is divided into a plurality of cylindrical specimens, the height-to-diameter ratio of the cylindrical specimen is 2:1, the height is 6 mm, and the diameter is 3 mm. The cylindrical specimens are subjected to uniaxial compression using a universal testing machine, and a constant compression rate of 0.25 mm / min is maintained during the uniaxial compression. The blank B is subjected to radial compression, and the arc loading angle of the radial compression mold used during the radial compression is 20°. The experimental constant compression rate is 0.25 mm / min, and the two fracture strengths under the 7 pressures are calculated respectively;

[0052] Step 4: Calculate and analyze the data obtained in step 3, input it into the finite element software for simulation calculation, and output the simulated density cloud map; the specific process is:

[0053] Step 4.1. Calculate the Drucker-Prager / Cap model by fracture strength, such as cohesion d = 10, friction angle β = 1.172 rad and hardening curve related to volume plasticity in represents the volumetric plastic strain; and the geometric shape parameter R and the shape parameter α of the transition zone related to the model are 0.6 and 0.03, respectively. The Young's modulus, Poisson's ratio and friction coefficient of Cu powder are 129.8 GPa, 0.343 and 0.329, respectively;

[0054] Step 4.2. Cohesion d, friction angle β and hardening curve P related to volume plasticity b Input the Drucker-Prager / Cap model into the finite element software, and use the actual rolling mill as a prototype to build a rigid roll in the finite element software with a diameter of 114 mm;

[0055] Step 4.3, use two rigid rollers in the finite element software to simulate the three stages of the rolling process, the first stage is the free flow zone, the second stage is the bite zone, and the third stage is the deformation and hardening zone; in the second stage, a deformable body curved trapezoidal model is established in the bite zone with a bite angle of 7°, and the Drucker-Prager / Cap model parameters are assigned to the deformable body curved trapezoidal model, and its mesh type is an 8-node hexahedral linear reduced integration unit; adjust the rolling speed and rolling gap of the rigid rollers, and output a simulated density cloud map that is close to the ideal density cloud map.

[0056] Step 5: direct powder rolling parameters are guided according to the electrolytic Cu powder particle size, rolling speed and rolling gap corresponding to the simulated density cloud map output in step 4.

[0057] Weigh 25 g of the mixed powder A in step 1 for later use, and pour the powder into the rolling mill from the funnel equipped above the rolling mill. Before the direct powder rolling experiment begins, the rolling gap is measured by a feeler gauge to be 0.1 mm, and the rolling speed is set to 35 rpm. The density distribution cloud diagram and macroscopic morphology of the copper sheet prepared in Example 1 of the present invention are shown in FIG. Figure 2a-2c As shown in the figure, the green density distribution cloud diagram obtained by direct powder rolling process is output by the post-processing function of finite element software. Figure 2a As shown in Figure 2, it can be seen that the overall distribution is in the shape of a "tongue". The macroscopic morphology of the copper sheet obtained by direct powder rolling experiment is shown in Figure 2. Figure 2b As shown in Figure 2, the green sheet is cut into regions, each of which is 10×10 mm in size. The density of each green sheet is measured using the Archimedean principle, and its actual density distribution cloud map is drawn as shown in Figure 2c. The average density value is 6.3 g / cm 3 .

[0058] Example 2

[0059] The present invention provides a method for preparing a copper alloy thin plate by direct powder rolling with computer-aided design, which is specifically implemented according to the following steps:

[0060] Step 1, weighing electrolytic Cu powders with particle sizes of 150 μm and 74 μm, the mass ratio of which is 2:1, the mass ratio of electrolytic Cu powder to zirconia balls is 1:1, the ratio of large balls to small balls is 4:1, the diameter of the large balls is 10 mm, and the diameter of the small balls is 5.5 mm; putting the electrolytic Cu powder and zirconia balls into a mixing bottle of a three-dimensional vibration mixer and mixing for 2 hours, the vibration frequency of the mixer during mixing is 40 Hz, to obtain mixed powder A;

[0061] The mass ratio of electrolytic Cu powder with particle size of 150μm and 74μm is 2:1. The mass ratio will affect the fluidity of the powder, and the fluidity will affect the forming quality of the copper sheet. When the mass ratio is 2:1, the forming quality of the copper sheet is better.

[0062] Step 2: Select multiple YG8 carbide steel molds with a diameter of 25 mm, put the mixed powder A into the molds respectively, set the pressure to 110 MPa, 160 MPa, 210 MPa, 260 MPa, 310 MPa, and 360 MPa, apply the above-mentioned different pressures to different molds respectively, maintain uniform pressure during the pressing process, and hold the pressure for 1 min to obtain the green body B under 6 pressures.

[0063] Step 3, the blank B under 6 pressures is divided into multiple cylindrical specimens, the height-to-diameter ratio of the cylindrical specimen is 2:1, the height is 6 mm, and the diameter is 3 mm. The cylindrical specimens are uniaxially compressed by a universal testing machine, and a constant compression rate of 0.25 mm / min is maintained during uniaxial compression. The blank B is radially compressed, and the arc loading angle of the radial compression mold used during radial compression is 20°. The constant compression rate of the experiment is 0.25 mm / min, and the two fracture strengths under 6 pressures are calculated respectively;

[0064] Step 4: Calculate and analyze the data obtained in step 3, input it into the finite element software for simulation calculation, and output the density cloud map; the specific process is:

[0065] Step 4.1. Calculate the cohesion d = 4, friction angle β = 1.211 rad and hardening curve related to volume plasticity in the Drucker-Prager / Cap model by fracture strength in Representing the volumetric plastic strain, as well as the geometric shape parameter R associated with the model and the shape parameter α of the transition zone are 0.6 and 0.03, respectively, and the Young's modulus, Poisson's ratio, and friction coefficient of Cu powder are 129.8 GPa, 0.343, and 0.329, respectively;

[0066] Step 4.2. Cohesion d, friction angle β and hardening curve P related to volume plasticity bInput the Drucker-Prager / Cap model into the finite element software, and use the actual rolling mill as a prototype to build a rigid roll in the finite element software with a diameter of 114 mm;

[0067] Step 4.3, use two rigid rollers in the finite element software to simulate the three stages of the rolling process, the first stage is the free flow zone, the second stage is the bite zone, and the third stage is the deformation and hardening zone; in the second stage, a deformable body curved trapezoidal model is established in the bite zone with a bite angle of 7°, and the Drucker-Prager / Cap model parameters are assigned to the deformable body curved trapezoidal model, and its mesh type is an 8-node hexahedral linear reduced integration unit; adjust the rolling speed and rolling gap of the rigid rollers, and output a simulated density cloud map that is close to the ideal density cloud map.

[0068] Step 5: direct powder rolling parameters are guided according to the electrolytic Cu powder particle size, rolling speed and rolling gap corresponding to the simulated density cloud map output in step 4.

[0069] Weigh 25 g of the mixed powder A in step 1 for later use, and pour the powder into the funnel equipped above the rolling mill. Before the direct powder rolling experiment begins, use a feeler gauge to measure the rolling gap to 0.2 mm, and set the rolling speed to 50 rpm. The density distribution cloud diagram and macroscopic morphology of the copper sheet prepared in Example 2 of the present invention are shown in FIG. Figure 3a-3c As shown in the figure, the green density distribution cloud diagram obtained by direct powder rolling process is output by the post-processing function of finite element software. Figure 3a As shown in Figure 2, it can be seen that the overall distribution is in the shape of a "tongue". The macroscopic morphology of the copper sheet obtained by direct powder rolling experiment is shown in Figure 2. Figure 3b As shown, it is cut into regions, each region is 10×10 mm in size, and the density of each green sheet is measured using the Archimedean principle, and its actual density distribution cloud map is drawn as shown in Figure 3c As shown, the average density is 7.5g / cm 3 .

[0070] Example 3

[0071] The present invention provides a method for preparing a copper alloy thin plate by direct powder rolling with computer-aided design, which is specifically implemented according to the following steps:

[0072] Step 1, weighing electrolytic Cu powders with particle sizes of 150 μm and 74 μm, the mass ratio of which is 1:2, the mass ratio of electrolytic Cu powder to zirconia balls is 1:1, the ratio of large balls to small balls is 4:1, the diameter of the large balls is 9 mm, and the diameter of the small balls is 5 mm; putting the electrolytic Cu powder and zirconia balls into a mixing bottle of a three-dimensional vibration powder mixer and mixing for 2 hours, the vibration frequency of the powder mixer during mixing is 40 Hz, to obtain mixed powder A;

[0073] Step 2: Select multiple YG8 carbide steel molds with a diameter of 25 mm, put the mixed powder A into the molds respectively, set the pressure to 130 MPa, 180 MPa, 230 MPa, 280 MPa, 330 MPa, and 380 MPa, apply the above-mentioned different pressures to different molds respectively, maintain uniform pressure during the pressing process, and hold the pressure for 1 min to obtain the green body B under 6 pressures.

[0074] Step 3, the blank B under 6 pressures is divided into multiple cylindrical specimens, the height-to-diameter ratio of the cylindrical specimen is 2:1, the height is 6 mm, and the diameter is 3 mm. The cylindrical specimens are uniaxially compressed by a universal testing machine, and a constant compression rate of 0.25 mm / min is maintained during uniaxial compression. The blank B is radially compressed, and the arc loading angle of the radial compression mold used during radial compression is 20°. The constant compression rate of the experiment is 0.25 mm / min, and the two fracture strengths under 6 pressures are calculated respectively;

[0075] Step 4: Calculate and analyze the data obtained in step 3, input it into the finite element software for simulation calculation, and output the density cloud map; the specific process is:

[0076] Step 4.1: Calculate the relevant parameters in the Drucker-Prager / Cap model through the fracture strength, such as cohesion d = 3.09, friction angle β = 1.191 rad and the hardening curve related to volume plasticity in Representing the volumetric plastic strain, as well as the geometric shape parameter R associated with the model and the shape parameter α of the transition zone are 0.6 and 0.03, respectively, and the Young's modulus, Poisson's ratio, and friction coefficient of Cu powder are 129.8 GPa, 0.343, and 0.329, respectively;

[0077] Step 4.2. Cohesion d, friction angle β and hardening curve P related to volume plasticity b Input the Drucker-Prager / Cap model into the finite element software, and use the actual rolling mill as a prototype to build a rigid roll in the finite element software with a diameter of 114 mm;

[0078] Step 4.3, use two rigid rollers in the finite element software to simulate the three stages of the rolling process, the first stage is the free flow zone, the second stage is the bite zone, and the third stage is the deformation and hardening zone; in the second stage, a deformable body curved trapezoidal model is established in the bite zone with a bite angle of 8°, and the Drucker-Prager / Cap model parameters are assigned to the deformable body curved trapezoidal model, and its mesh type is an 8-node hexahedral linear reduced integration unit. Adjust the rolling speed and rolling gap of the rigid rollers, and output a simulated density cloud map that is close to the ideal density cloud map.

[0079] Step 5: direct powder rolling parameters are guided according to the electrolytic Cu powder particle size, rolling speed and rolling gap corresponding to the simulated density cloud map output in step 4.

[0080] Weigh 25 g of the mixed powder A in step 1 for later use, and pour the powder into the rolling mill from the funnel provided above the rolling mill. Before the direct powder rolling experiment begins, the rolling gap is measured to be 0.25 mm by a feeler gauge, and the rolling speed is set to 40 rpm. The density distribution cloud diagram and macroscopic morphology of the copper sheet prepared in Example 3 of the present invention are shown in FIG. Figure 4a-4c As shown in the figure, the green density distribution cloud diagram obtained by direct powder rolling process is output by the post-processing function of finite element software. Figure 4a As shown in Figure 1, it can be seen that the overall distribution is in the shape of a "tongue". The macroscopic morphology of the copper sheet obtained by direct powder rolling experiment is shown in Figure 1. Figure 4b As shown, it is cut into regions, each region is 10×10 mm in size, and the density of each green sheet is measured using the Archimedean principle, and its actual density distribution cloud map is drawn as shown in Figure 4c As shown, the average density is 5.73 g / cm 3 .

[0081] Example 4

[0082] The present invention provides a method for preparing a copper alloy thin plate by direct powder rolling with computer-aided design, which is specifically implemented according to the following steps:

[0083] Step 1, weighing electrolytic Cu powder with a particle size of 74 μm and zirconia balls, the mass ratio of electrolytic Cu powder to zirconia balls is 1:1, the ratio of large balls to small balls is 4:1, the diameter of the large balls is 11 mm, and the diameter of the small balls is 6 mm; putting the electrolytic Cu powder and zirconia balls into a mixing bottle of a three-dimensional vibration mixer and mixing for 2 hours, the vibration frequency of the mixer during mixing is 40 Hz, to obtain mixed powder A;

[0084] Step 2: Select multiple YG8 carbide steel molds with a diameter of 25 mm, put the mixed powder A into the molds respectively, set the pressure to 130 MPa, 180 MPa, 230 MPa, 280 MPa, 330 MPa, and 380 MPa, apply the above-mentioned different pressures to different molds respectively, maintain uniform pressure during the pressing process, and hold the pressure for 1 min to obtain the green body B under 6 pressures.

[0085] Step 3, the blank B under 6 pressures is divided into multiple cylindrical specimens, the height-to-diameter ratio of the cylindrical specimen is 2:1, the height is 6 mm, and the diameter is 3 mm. The cylindrical specimens are uniaxially compressed by a universal testing machine, and a constant compression rate of 0.25 mm / min is maintained during uniaxial compression. The blank B is radially compressed, and the arc loading angle of the radial compression mold used during radial compression is 20°. The constant compression rate of the experiment is 0.25 mm / min, and the two fracture strengths under 6 pressures are calculated respectively;

[0086] Step 4: Calculate and analyze the data obtained in step 3, input it into the finite element software for simulation calculation, and output the density cloud map; the specific process is:

[0087] Step 4.1. Calculate the cohesion d = 7.45, friction angle β = 1.184 rad and hardening curve related to volume plasticity in the Drucker-Prager / Cap model by fracture strength in represents the volumetric plastic strain. The geometric shape parameter R and the shape parameter α of the transition zone related to the model are 0.6 and 0.03, respectively. The Young's modulus, Poisson's ratio and friction coefficient of Cu powder are 129.8 GPa, 0.343 and 0.329, respectively.

[0088] Step 4.2. Cohesion d, friction angle β, and hardening curve P related to volume plasticity b Input the Drucker-Prager / Cap model into the finite element software, and use the actual rolling mill as a prototype to build a rigid roll in the finite element software with a diameter of 114 mm;

[0089] Step 4.3, use two rigid rollers in the finite element software to simulate the three stages of the rolling process, the first stage is the free flow zone, the second stage is the bite zone, and the third stage is the deformation and hardening zone; in the second stage, a deformable body curved trapezoidal model is established in the bite zone with a bite angle of 9°, and the Drucker-Prager / Cap model parameters are assigned to the deformable body curved trapezoidal model, and its mesh type is an 8-node hexahedral linear reduced integration unit, i.e. C3D8R; adjust the rolling speed and rolling gap of the rigid roller, and output a simulated density cloud map that is close to the ideal density cloud map.

[0090] Step 5: direct powder rolling parameters are guided according to the electrolytic Cu powder particle size, rolling speed and rolling gap corresponding to the simulated density cloud map output in step 4.

[0091] Weigh 25 g of the mixed powder A in step 1 for later use, and pour the powder into the rolling mill from the funnel equipped above the rolling mill. Before the direct powder rolling experiment begins, the rolling gap is measured by a feeler gauge to be 0.2 mm, and the rolling speed is set to 40 rpm. The density distribution cloud diagram and macroscopic morphology of the copper sheet prepared in Example 4 of the present invention are shown in FIG. Figure 5a-5c As shown in the figure, the green density distribution cloud diagram obtained by direct powder rolling process is output by the post-processing function of finite element software. Figure 5a As shown in Figure 1, it can be seen that the overall distribution is in the shape of a "tongue". The macroscopic morphology of the copper sheet obtained by direct powder rolling experiment is shown in Figure 1. Figure 5b As shown in Figure 5, the green sheet is cut into regions, each of which is 10×10 mm in size. The density of each green sheet is measured using the Archimedean principle, and its actual density distribution cloud map is drawn as shown in Figure 5c. The average density value is 4.51 g / cm 3 .

[0092] By Examples 2a-5c, and the attached Figure 2a-5c It can be seen that the density and morphology of the copper alloy thin plate obtained by the computer-aided direct powder rolling preparation method of the present invention are consistent with the copper alloy thin plate obtained by the actual direct powder rolling process, and the order of influence of various process factors on the green billet forming quality is powder gradation> rolling speed> rolling gap. Under the guidance of the direct powder rolling simulation results, the average relative density of the green billet obtained by the direct powder rolling experiment is 7.5-8.0 g / cm 3 , which is higher than 80% of the theoretical density. Its strength meets the transfer process of the sintering process, and the thin plate will not break. The modeling method, physical parameter acquisition method and numerical simulation results can be used to guide the rapid forming of the direct powder rolling process. The present invention provides basic knowledge for the direct rolling process of metal powder and provides theoretical guidance for the preparation of low-cost and high-efficiency IC lead frames.

Claims

1. A computer-aided design method for preparing copper alloy thin plates by direct powder rolling, characterized in that: Follow the steps below to implement it: Step 1, weighing electrolytic Cu powder and zirconium oxide balls with a particle size of 150 μm-74 μm, putting the electrolytic Cu powder and zirconium oxide balls into a mixing bottle of a three-dimensional vibration powder mixer and mixing for 2 hours, the vibration frequency of the powder mixer during mixing is 40 Hz, to obtain mixed powder A; Step 2: Put the mixed powder A into the mold, adjust various pressures and press them respectively to form the green bodies B corresponding to the various pressures; Step 3, the blank B is divided into a plurality of cylindrical specimens, and the cylindrical specimens are subjected to uniaxial compression by a universal testing machine, and the blank B is subjected to radial compression, and two fracture strengths are calculated respectively; Step 4, calculating and analyzing the fracture strength obtained in step 3, inputting it into finite element software for simulation calculation, and outputting a simulation density cloud map; Step 5, adjusting parameters, and determining guiding direct powder rolling parameters according to the simulated density cloud map; The mass ratio of the electrolytic Cu powder to the zirconia ball in step 1 is 1:1, the ratio of the large ball to the small ball is 4:1, the diameter of the large ball is 9-11 mm, and the diameter of the small ball is 5-6 mm; The specific process of step 2 is as follows: select multiple YG8 carbide steel molds with a diameter of 25 mm, put the mixed powder A into the molds respectively, set multiple pressure values ​​in the range of 100-400 MPa, and the pressure difference between two adjacent values ​​is 50 MPa. Apply different pressures to each mold respectively, maintain uniform pressure during the pressing process, and hold the pressure for 1 min to obtain the green body B under multiple pressures; The height-to-diameter ratio of the cylindrical sample in step 3 is 2:1, the height is 6 mm, the diameter is 3 mm, and the compression rate is kept constant at 0.25 mm / min during the uniaxial compression; The arc loading angle of the radial compression die used in the radial compression in step 3 is 20 o , the experimental constant compression rate is 0.25mm / min; The specific process of step 4 is as follows: Step 4.

1. Calculate the cohesion in the Drucker-Prager / Cap model from the fracture strength d , friction angle β, and the hardening curve P associated with volume plasticity b ; Step 4.2: Cohesion d , friction angle β and the hardening curve P associated with volume plasticity b Input the Drucker-Prager / Cap model into the finite element software, and use the actual rolling mill as a prototype to establish a rigid roll in the finite element software; Step 4.3: Use two rigid rollers in the finite element software to simulate the three stages of the rolling process. The first stage is the free flow zone, the second stage is the bite zone, and the third stage is the deformation and hardening zone. In the second stage, a deformable curved trapezoidal model is established in the bite zone with a bite angle range of 7-9. o , assign the Drucker-Prager / Cap model parameters to the deformable curved trapezoidal model, and its mesh type is 8-node hexahedral linear reduced integration unit; set the rolling speed of the rigid roller to 35-50rpm, the rolling gap to 0.1-0.25mm, and output the simulated density cloud map; The adjustment parameters in step 5 refer to adjusting the particle size of the electrolytic Cu powder, the rolling speed of the rigid roller, and the rolling gap.